Compositional and biogeochemical variations of sediments across the terrestrial-marine continuum of the Baker-Martínez fjord system (Chile, 48°S). (May 2019) - Rebolledo, Lorena; Bertrand, Sebastien; Lange, Carina B.; Tapia, Fabian J.; Quiroga, Eduardo; Troch, Matthias; Silva, Nelson; Cárdenas, Paola; Pantoja, Silvio
Graphical abstract: Highlights: The Baker-Martinez fjord system covers a complete terrestrial-to-marine continuum. Variability in sediment composition is mostly explained by distance from river mouths. Ntot /Corg measurements are strongly affected by glacial clay input. δ 13 Corg and freshwater diatoms are the best indicators of terrestrial input. Abstract: The Baker-Martínez fjord system (Chile, 48°S) is a transitional environment between the terrestrial ecosystems of Patagonia and the SE Pacific Ocean. This unique setting makes it an ideal system to evaluate land-ocean gradients in sediment composition and in a range of biogeochemical variables. Here, we studied the composition and organic geochemistry of surface sediments deposited in the Baker-Martínez fjord system to assess spatial changes in sediment properties and identify the best tracers of terrestrial input. We determined concentrations in biogenic opal, organic carbon, calcium carbonate, and lithogenic particles, and we measured diatom abundance, bulk elemental and isotopic organic geochemistry, and n- alkanes distribution, on a series of surface sediment samples distributed along two proximal-to-distal transects (one in the Martínez Channel and a second one in the Baker Channel). Results reveal clear proximal-to-distal trends in the proportion of freshwater diatoms and in the fraction of organic carbon of terrestrial origin calculated from the bulk organic δ 13 C measurements. Diatoms are particularly sensitive to freshwater input in proximal environments, whereas bulk organic geochemistry better reflects terrestrial input over long distances across the fjord system. Other terrestrial proxies frequently used in the literature, such as the N/C ratio and the n -alkane-based terrestrial/aquatic ratio, did not show clear variations with distance from the fjord head. Our results suggest that the isotopic composition of bulk organic matter (δ 13 Corg ) and the relative proportion of diatoms of freshwater origin are the best-suited proxies to estimate past changes in terrestrial input from fjord sediment archives, irrespective of the glacial status of the fjord and its watershed.